PELATIHAN MEMBATIK MOTIF MINANGKABAU: SARANA UNTUK MENINGKATKAN MINAT WIRAUSAHA MASYARAKAT DI NAGARI KAMANG MUDIAK KABUPATEN AGAM - Devi Yulia Rahmi; Asniati Asniati; Jefril Rahmadoni; Khairil Anwar (Jurnal Hilirisasi IPTEKS, 2023)
Entrepreneurship is an innovative and creative process of creating products or services that add value. Entrepreneurial interest can arise with activities that train interest. This activity aims to help PKK (Family Welfare Development) Nagari Kamang Mudiak to have creativity in creating business opportunities in the form of batik. The word batik is thought to have come from the word 'ambatik', which translated means 'fabric with small dots'. Batik training activities are carried out using lectures, practice, and discussions. The batik training was held at the ZUMFAKEYA Nagari Kamang Mudiak Training Center, Kamang Magek District, Agam Regency. Participants are PKK in Nagari Kamang Mudiak. The batik training was held on Sunday, 06 November 2022. In the initial stages, the service team coordinated with the Nagari government to gather the Nagari Kamang Mudiak community. Then continue doing batik training with the tools and materials provided by the service team. The carrying out of batik training for the Nagari Kamang Mudiak community was also attended by the Head of the Agam Regency PKK, Wali Nagari Kamang Mudiak, several community leaders, and of course, the Nagari Kamang Mudiak community. Based on field analysis, the people of Nagari Kamang Mudiak already have basic skills in batik. The results of this training activity made the community very enthusiastic. They realized that entrepreneurial interest could arise from batik training activities and the firm will of the batik training participants. The conclusion from this activity showed that several PKK mothers could make batik (canting and colouring). It is hoped that this training can be carried out on an ongoing basis and become a type of business for PKK in Nagari Kamang Mudiak in general.